Obligation to Use Rupiah in Business Transactions in Indonesia - Indrawati, Etty; Windajani, E. Imma Indra Dewi; Kastowo, C.; Shalom, Efraim Yehuda (Westscience Press, 2024)
The Unitary State of the Republic of Indonesia as an independent and sovereign country, has a currency as a symbol of state sovereignty that must be respected and proud of by all Indonesian citizens. The rupiah is the currency of the Unitary State of the Republic of Indonesia which applies as a mandatory and legal payment instrument in the territory of the Unitary State of the Republic of Indonesia. However, there are areas in Indonesia that do not use Indonesian currency (Rupiah) as the main instrument of business transactions, especially in the border area between Indonesia and Malaysia. This raises the issue of the circulation of foreign currency as a tool for business transactions in the territory of Indonesia, which in turn creates competition between Rupiah and Ringgit in the economic circulation of the community in Indonesia. The purpose of this study is to determine the preventive and repressive efforts that can be made by the Indonesian government and Bank Indonesia to minimize violations of the use of foreign currencies in the territory of Indonesia, as regulated in Law Number 7 of 2011 concerning Currencies and Bank Indonesia Regulation Number 17/3/PBI/2015 concerning Obligations to Use Rupiah in the Territory of the Unitary State of the Republic of Indonesia. This research is normative legal research through library research by tracing secondary data in the form of primary legal materials, secondary legal materials, and tertiary legal materials, using documentation methods and instruments in the form of document studies. Then, the data were analyzed using qualitative analysis. The results of this research indicate that some preventive efforts can be made by the government and Bank Indonesia. The first is strengthening juridical instruments by the Government and Bank Indonesia. The second is the government together with Bank Indonesia must carry out a socialization and education movement related to the obligation to use Rupiah currency. The third is the government must build economic infrastructure facilities. The fourth is the government and Bank Indonesia can encourage the public to use Rupiah currency in electronic and digital forms. In this research, repressive efforts are not needed, because they can be resolved with preventive efforts, except in certain offenses that threaten the country's economic turnover or endanger the existence of the Rupiah currency on a massive scale.